Предмет: Алгебра,
автор: Frimoni22
Решите уравнение используя метод введения новой переменной
(x²+3x+1)(x²+3x+3)=-1
Ответы
Автор ответа:
0
x²3x+1=t
t(t+2)=-1
t²+2t+1=0
(t+1)²=0
t+1=0
t=-1
x²+3x+1=-1
x²+3x+2=0
x1+x2=-3 U x1*x2=2
x1=-2 U x2=-1
t(t+2)=-1
t²+2t+1=0
(t+1)²=0
t+1=0
t=-1
x²+3x+1=-1
x²+3x+2=0
x1+x2=-3 U x1*x2=2
x1=-2 U x2=-1
Похожие вопросы
Предмет: Русский язык,
автор: ragabyev78
Предмет: Математика,
автор: mahliesaparbaeva
Предмет: Математика,
автор: valeriasutula8
Предмет: История,
автор: kis28102002Nastia
Предмет: Биология,
автор: piggeta